PTH-021 Reassessing The Value of Gastroscopy for The Investigation of Dyspepsia. (17th August 2016) - Ching, H-L; Hale, MF; Sidhu, R; McAlindon, ME
Abstract : Introduction: The National Institute of Health and Clinical Excellence (NICE) first recommended a policy of H. pylori test and treat or empirical full dose proton pump inhibitor therapy for uninvestigated dyspepsia in 2004. 1 Following an initial fall in demand for gastroscopy (OGD), there has been a 30% increase in the last five years. 2 Whilst regarded as the gold standard, it is uncomfortable, costly, may require sedation and carries the risks of intubation. In an era when non-invasive tests are emerging, the role of OGD requires re-evaluation. Methods: Data from consecutive OGDs performed between September 2015 and January 2016 to investigate dyspepsia was analysed. We determined the percentage of patients in whom OGD ± biopsy changed management as defined by an approach other than the non-invasive NICE recommendations. 1 Results: 500 patients (39.8% male; mean age 58±16.1) underwent OGD for dyspepsia, some of whom also had dysphagia (6%), anaemia (4%), vomiting (4.2%) or suspected gastrointestinal (GI) bleeding (0.6%). 145 (29%) were sedated (midazolam (mean±SEM) 2.0 mg±1.0; fentanyl (when used) 50 mcg±23). 381 patients (76.2%) had abnormal endoscopy; 417 (83.4%) had biopsies taken (15.8% for histological assessment, 27.4% for rapid urease tests, 40.2% for both). Findings of uncertain relevance, or which could have been managed with empirical therapies, were seen in 299 patients (59.8%; including oesophagitis (n = 122), hiatus hernias (n = 178), gastric polyps (n = 34), gastritis (n = 236), gastric ulcers (n = 9), gastric erosions (n = 32), duodenitis (n = 40), duodenal ulcer (n = 1), duodenal erosions (n = 15) and a duodenal polyp (n = 1)). Diagnoses which would not have been appropriately managed by empirical therapies numbered 82 (16.4%). These included 71 (14.2%) patients with Barrett's oesophagus (n = 39), oesophageal stricture (n = 2), oesophageal cancer (n = 1) and gastric cancer (n = 4) diagnosed at the time of endoscopy. An additional 11 (2.2%) diagnoses were made solely by histology, which included eosinophilic oesophagitis (n = 1), eosinophilic gastritis (n = 1), intestinal metaplasia (n = 3) and coeliac disease (n = 6). Conclusion: Diagnoses which alter management are made by endoscopy in only 14.2% of patients with dyspepsia. Although the majority of patients have biopsies taken, the added value increases the yield to only 16.4%. Non-invasive, cost-effective diagnostic strategies are needed to better guide patient management and select the minority of patients who need endoscopic biopsy or therapy. References: 1 www.nice.org.uk/guidance/CG184 (2014 update) 2 https://www.england.nhs.uk/statistics Disclosure of Interest: None Declared